Everyday sunscreen use may compromise vitamin D in temperate climes. (11th February 2020) - de Gruijl, F.R.; Webb, A.R.; Rhodes, L.E.
Abstract : Linked Article: Passeron et al . Br J Dermatol 2019; 181:916–31.